Extracellular vesicles derived from cardiosphere-derived cells as a potential antishock therapeutic. Issue 2 (August 2021) - Chance, Tiffani C.; Wu, Xiaowu; Keesee, Jeffrey D.; Garcia-Marcano, Josue; Salgado, Christi L.; Liu, Bin; Moseley, Jennifer J.; Peck, Kiel A.; R.-Borlado, Luis; Atai, Nadia A.; Gould, Stephen J.; Marban, Linda S.; et al.
Abstract : BACKGROUND: Extracellular vesicles (EVs) isolated from cardiosphere-derived cells (CDC-EVs) are coming to light as a unique cell-free therapeutic. Because of their novelty, however, there still exist prominent gaps in knowledge regarding their therapeutic potential. Herein the therapeutic potential of CDC-EVs in a rat model of acute traumatic coagulopathy induced by multiple injuries and hemorrhagic shock is outlined. METHODS: Extracellular vesicle surface expression of procoagulant molecules (tissue factor and phosphatidylserine) was evaluated by flow cytometry. Extracellular vesicle thrombogenicity was tested using calibrated thrombogram, and clotting parameters were assessed using a flow-based adhesion model simulating blood flow over a collagen-expressing surface. The therapeutic efficacy of EVs was then determined in a rat model of acute traumatic coagulopathy induced by multiple injuries and hemorrhagic shock. RESULTS: Extracellular vesicles isolated from cardiosphere-derived cells are not functionally procoagulant and do not interfere with platelet function. In a rat model of multiple injuries and hemorrhagic shock, early administration of EVs significantly reduced the elevation of lactate and creatinine and did not significantly enhance coagulopathy in rats with acute traumatic coagulopathy. CONCLUSION: The results of this study are of great relevance to the development of EV products for use in combat casualty care, as our studies show that CDC-EVs have the potential to be an antishock therapeutic if administered early. These results demonstrate that research using CDC-EVs in trauma care needs to be considered and expanded beyond their reported cardioprotective benefits. Abstract : Supplemental digital content is available in the text.